2017
DOI: 10.4172/2165-8064.1000308
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Sustainable Raw Materials for Sanitary Napkin

Abstract: The present paper highlights the issue of non-biodegradability of personal hygiene product and how it has become a serious environmental concern all over the world. Emphasis is given to use naturally available absorbent fibres such as organic cotton, banana fibre, jute, bamboo etc., which are widely available and biodegradable in nature having low carbon footprint which not only makes it eco-friendly but also reduces the cost of sanitary pad. And to enhance the retention of fluid cellulose based hydro gel can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Bamboo has good overall moisture management capability, which classifies the material as water penetration fabrics with small spreading area [28]. A recent study found that bamboo fibre as an absorbent core in a traditional sanitary napkin format absorbs and wicks water 3-4-fold better than cotton and reduces odour as the fibre is filled with multiple micro-holes and micro-gaps [29]. Thus, the use of bamboo fibres as a core of sanitary pads is a good alternative compared to SAP and, moreover, it is biodegradable in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Bamboo has good overall moisture management capability, which classifies the material as water penetration fabrics with small spreading area [28]. A recent study found that bamboo fibre as an absorbent core in a traditional sanitary napkin format absorbs and wicks water 3-4-fold better than cotton and reduces odour as the fibre is filled with multiple micro-holes and micro-gaps [29]. Thus, the use of bamboo fibres as a core of sanitary pads is a good alternative compared to SAP and, moreover, it is biodegradable in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Bamboo has good overall moisture management capability, which classi es the material as water penetration fabrics with small spreading area [ 25 ]. A recent study found that bamboo bre as an absorbent core in a traditional sanitary napkin format absorbs and wicks water 3-4 times better than cotton and reduces odour as the bre is lled with multiple micro-holes and micro-gaps [ 26 ]. Thus, the use of bamboo bres as a core of sanitary pads is a good alternative compared to SAP and moreover, it is biodegradable in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Bamboo wadding is the most suited material for clean items since it is approximately twice as absorbent as a commercial sanitary pad, incredibly absorbent, inexpensive, lightweight, and biodegradable. It has no negative impacts on the user or the environment [21].…”
Section: Plant-based Sanitary Padmentioning
confidence: 99%